124 MODELING BARTH SYNDROME IN ZEBRAFISH. (1st January 2005) - Strauss, A. W.; Khuchua, Z.; Miller, J.; Yue, Z.; Appel, B.
Abstract : Purpose: Barth syndrome is an X-linked genetic disorder characterized by dilated cardiomyopathy, skeletal myopathy, cyclic neutropenia, organic aciduria and growth retardation. Human Barth syndrome is associated with mutations in tafazzin (TAZ) gene located on Xq28. The function of TAZ is unknown, although the protein has a high degree of homology with acyl-transferases, suggesting a role in mitochondrial cardiolipin metabolism. Our goal was to develop an animal model of this disorder to define functions of the TAZ gene. Methods: Western blot analysis with antibodies against the C-terminal TAZ domain was done. To elucidate the role of G4.5 gene in development, we blocked translation of tafazzin mRNA in zebrafish (Danio rerio) by injecting a morpholino antisense oligonucleotide into freshly-fertilized eggs. Results: The immunoblot demonstrated that TAZ is located in mitochondria and forms high-molecular weight complexes. In the zebrafish knockdown, after 51 hours, the embryos exhibited severe growth and developmental abnormalities and marked bradycardia. The heart was dilated with pericardial edema, consistent with congestive heart failure. (figure ) Conclusions: This phenotype resembles human Barth syndrome. Our results show that G4.5 gene is essential for normal cardiac development in zebrafish and provide a model for more detailed characterization of the biochemical phenotype.